A Thermodynamic Comparison of Nanotip and Nanoblade Geometries for Ultrafast Laser Field Emission via the Finite Element Method - Joshua Mann; James Rosenzweig (Physics, 2023)
Strong laser field emission from metals is a growing area of study, owing to its applications in high-brightness cathodes and potentially as a high harmonic generation source. Nanopatterned plasmonic cathodes localize and enhance incident laser fields, reducing the spot size and increasing the current density. Experiments have demonstrated that the nanoblade structure outperforms nanotips in the peak fields achieved before damage is inflicted. With more intense surface fields come brighter emissions, and thus investigating the thermomechanical properties of these structures is crucial in their characterization. We study, using the finite element method, the electron and lattice temperatures for varying geometries, as well as the opening angles, peak surface fields, and apex radii of curvature. While we underestimate the energy deposited into the lattice here, a comparison of the geometries is still helpful for understanding why one structure performs better than the other. We find that the opening angle—not the structure dimensionality—is what primarily determines the thermal performance of these structures.